(untitled) (Journal of Scientific Research, 2013)
A rapid and highly sensitive reversed phase high performance liquid chromatographic method has been developed for quantitative estimation of omeprazole in pharmaceutical preparations. The method has been validated according to FDA and USP guidelines with respect to accuracy, precision, specificity and linearity. The method was developed by using a gradient condition of mobile phase comprising 90% aqueous acetonitrile to 100% acetonitrile for 10 minutes at a flow rate of 0.7 mL/min over C-18 (ODS, 250 x 4.6 mm) column at ambient temperature. More than 97% recovery demonstrated the accuracy of the protocol. Intra-day and inter-day precision studies of the new method were less than the maximum allowable limit (RSD% £ 2.0 according to FDA). The method showed linear response with correlation coefficient (r2) value of 0.998. Therefore, it was found to be accurate, reproducible, sensitive and less time consuming and can be successfully applied for the assay of omeprazole formulations. Keywords: HPLC; Method development; Gradient condition; Validation; Omeprazole. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i2.12779 J. Sci. Res. 5 (2), 335-342 (2013)